A people's guide to Greater Boston - Nevins, Joseph; Moodliar, Suren, 1962-; Macrakis, Eleni, 1991- (University of California Press people's guides, 2020)
"Herein, we bring you to sites that have been central to the lives of 'the people' of Greater Boston over four centuries. You'll visit sites associated with the area's Indigenous inhabitants and with the individuals and movements who sought to abolish slavery, to end war, challenge militarism, and bring about a more peaceful world, to achieve racial equity, gender justice, and sexual liberation, and to secure the rights of workers. We take you to some well-known sites, but more often to ones far off the well-beaten path of the Freedom Trail, to places in Boston's outlying neighborhoods. We also visit sites in numerous other municipalities that make up the Greater Boston region-from places such as Lawrence, Lowell and Lynn to Concord and Plymouth. The sites to which we do 'travel' include homes given that people's struggles, activism, and organizing sometimes unfold, or are even birthed in many cases in living rooms and kitchens. Trying to capture a place as diverse and dynamic as Boston is highly challenging. (One could say that about any 'big' place.) We thus want to make clear that our goal is not to be comprehensive, or to 'do justice' to the region. Given the constraints of space and time as well as the limitations of knowledge--both our own and what is available in published form--there are many important sites, cities, and towns that we have not included. Thus, in exploring scores of sites across Boston and numerous municipalities, our modest goal is to paint a suggestive portrait of the greater urban area that highlights its long-contested nature. In many ways, we merely scratch the region's surface--or many surfaces--given the multiple layers that any one place embodies. In writing about Greater Boston as a place, we run the risk of suggesting that the city writ-large has some sort of essence. Indeed, the very notion of a particular place assumes intrinsic characteristics and an associated delimited space. After all, how can one distinguish one place from another if it has no uniqueness and is not geographically differentiated? Nonetheless, geographer Doreen Massey insists that we conceive of places as progressive, as flowing over the boundaries of any particular space, time, or society; in other words, we should see places as processual or ever-changing, as unbounded in that they shape and are shaped by other places and forces from without, and as having multiple identities. In exploring Greater Boston from many venues over 400 years, we embrace this approach. That said, we have to reconcile this with the need to delimit Greater Boston--for among other reasons, simply to be in a position to name it and thus distinguish it from elsewhere"--